Urbanization in the North? An Examination of Urban Land Cover/Land Use Change in Nunavut - Melanie MacDonald (2023)
This study examines population growth and artificial land cover change in Nunavut, Canada’s newest, largest, and northernmost territory. It provides a useful, repeatable methodological framework for identifying and analyzing urban change by analyzing GlobeLand30 (GLC30) data from 2000 and 2010. While previous studies have examined the accuracy of GLC30, this study uses the dataset for a regional analysis of a specific class of land cover/land use (i.e. artificial) in order to answer the question of whether or not urban growth is taking place. Results demonstrate that GLC30 data was useful in detecting the location of human settlements in Nunavut but not in measuring urban growth over time in absolute terms – combining land cover data with Census data was necessary to further examine the specific question of urbanization.